Immunoglobulin mRNA stability varies during B lymphocyte differentiation. - Jäck, H M (1988)
During differentiation of B lymphocytes, the change in the amount of immunoglobulin heavy chain produced is reflected by a change in the steady state level of heavy chain mRNA. At the pre-B cell stage, the earliest stage at which immunoglobulin chain is produced, and later at the small resting B cell stage, there is a low steady state level of heavy chain mRNA. After the small B cell has differentiated to become a plasma cell, the steady state level of heavy chain mRNA is much higher. We confirm that the transcription rate at the immunoglobulin mu heavy chain gene does not change during differentiation from the pre-B cell to the plasma cell stage. In contrast, we show here that differences in the stability of mu mRNA are sufficient to account for the differences in the steady state level at the various differentiation stages.